Effectiveness of corporate intranet in selected Malaysian companies. - Masrek, Mohamad Noorman; Jusoff, Kamaruzaman; Abdul Karim, Nor Shariza; Hussein, Ramlah (Canadian Center of Science and Education, 2009)
This study was undertaken with the purpose of measuring intranet effectiveness in selected Malaysian companies. Defining effectiveness as composite constructs of intranet characteristics, intranet usage and individual performance, the study employed a cross-sectional survey method. A total of 359 users participated in the study. The intranet characteristics namely, task fit, information quality and systems quality are found to be significantly related to intranet usage. Likewise the three intranet variables, namely, usage mode, usage for decision support and usage for knowledge sharing are also found to be significantly related to individual performance measured in terms of task innovation, task productivity and personal sense of accomplishment. Hence, the study had indeed confirmed that intranets users in Malaysian companies have perceived their intranet to be effective.